Case reportFrontotemporal lobar degeneration with MAPT mutation in an Italian-Polish family. A case report - Wierzba-Bobrowicz, Teresa; Lewandowska, Eliza; Zaremba, Jacek; Berdyński, Mariusz; Żekanowski, Cezary; Stępień, Tomasz; Felczak, Paulina; Tarka, Sylwia (Folia Neuropathologica, 2014)
Frontotemporal lobar degeneration (FTLD) with mutations in the MAPT (microtubule-associated protein tau) gene (FTLD with MAPT mutation) is a neurodegenerative disease with various clinical phenotypes. We present an Italian- Polish family with a IVS10+3G>A mutation in the MAPT gene, linked with haplotype H1s in a male proband (Fig. 2, II.2, H1s/H1b diplotype) and his sister (Fig. 2, II.1, the H1s/H1j diplotype). This report presents clinical, neuropathological and genetic testing of the proband and his affected sister, two members of an Italian-Polish family consisting of 25 family members. Their clinical history includes dementia as well as movement and cardiovascular disorders. Magnetic resonance imaging showed frontal and temporal cerebral atrophy. Neuropathological studies of the brain samples showed loss of neurons, gliosis, and the occurrence of neurofibrillary tangles, numerous neuropil threads, coiled bodies and abundant deposits of tau protein, including 3- and 4-repeated isoforms in neurons and glial cells. Only in the male proband brain, there were Pick body-like deposits in granule neurons of the hippocampus. Pathology of vascular walls was found in both cases. Ultrastructurally, the male proband showed clusters of collagen fibers mainly in a pericyte position. Beside the typical neurofibrillary pathology, aggregated gliofilaments and lipofuscin deposits in astroglia are described. Our report suggests that FTLD with IVS10+3G>A MAPT mutation causes damage mainly to the central nervous system and induces neuropathological changes, depending on the haplotypes of MAPT. In the clinical course of this disease, damage of the cardiovascular system may also be observed.